The development of audiotactile temporal perception - Stanley, Brendan M. (My University, 2023)
This thesis investigated developmental changes in temporal perception of hearing and touch (audiotactile). Three empirical chapters provide converging evidence on the unique characteristics of this modality pairing. In Chapter 2, a simultaneity judgment task assessed temporal perception. Three groups of children (aged 7-, 9-, and 11-years-old) were compared to a group of adults, examining measures such as the temporal simultaneity window and the point of subjective simultaneity. By age 11, mature temporal perception between hearing and touch was observed. Chapter 3 investigated developmental changes in temporal-based integration using the fission and fusion illusions. The study involved comparing three groups of children to adults (aged 9-, 11-, and 13-years-old). The measure of illusion strength combined with a signal detection analysis demonstrated that children did not exhibit adult-like integration until around age 13. Chapter 4 explored the potential impact of short-term congenital visual deprivation on hearing and touch temporal perception. An audiotactile simultaneity task was used to test a group of adults who received treatment for congenital bilateral cataracts. The results of this final experiment are considered preliminary because of limitations imposed by the COVID-19 pandemic; instead of the planned age- and gender-matched control participants, we utilized the adult data from Chapter 2 for comparison. The General Discussion provides a comprehensive account of how these findings relate to one another and how they situate in the broader literature. Additionally, a novel hypothetical theory is presented, incorporating the established causal inference framework, to offer insights into observed changes in multisensory perception across development.
Keywords: development; multisensory; temporal perception; audition; touch; audiotactile